ANTHOCYANIN STABILITY OF ROBUSTA COFFEE CHERRIES DURING STORAGE - Sukatiningsih Sukatiningsih; Windrati W S; Yudistira D (UPT Penerbitan Universitas Jember, 2012)
The overripe Robusta cherries had potential as a source of anthocyanin. The aim ofthis reseach was to investigated anthocyanin stability which extracted from cherries.Anthocyanin was extracted used ethanol and aquadest with ratio 1:1. Extraction wasrepeated 3 times untill the residue was colorless. After that this extract was kept at differenttemperature 5, 25 and 45 °C for 4 weeks. The stability was evaluated by content and lostanthocyanin, Hue color, pH and antioxidant activity. The result showed that during storageanthocyanin stability of all sample decreased. Sample which kept at 5 °C had the beststability with anthocyanin content 3.26 %,lost anthocyanin 26.55 %, Hue color 146.12, pH5.01 and antioxidant activity 16.26 % after 4 weeks. The least stability was obtained at samlple which kept at 45 °C with anthocyanin content 1.30 %, lost anthocyanin 29.02 % Hue color 124.92 ,pH 5.03 and antixidant activity 6.60 %.